Anti‐drug antibodies to brolucizumab and ranibizumab in serum and vitreous of patients with ocular disease. Issue 8 (28th February 2022) - Busch, Martin; Pfeil, Johanna M.; Dähmcke, Merlin; Brauckmann, Tara; Großjohann, Rico; Chisci, Viola; Hunfeld, Elisabeth; Eilts, Sonja; Omran, Wael; Morawiec‐Kisiel, Ewa; Schulz, Daniel; Paul, Sebastian; et al.
Abstract: Purpose: Postapproval reports of intraocular inflammation (IOI) and occlusive retinal vasculitis following intravitreal brolucizumab are accumulating. A role of anti‐drug antibodies (ADAs) to brolucizumab is under current scientific discussion. The purpose of the present study was to measure brolucizumab ADAs in a cross‐sectional ophthalmic patient population and to compare the occurrence of brolucizumab ADAs with that of ranibizumab ADAs. Methods: One hundred and ninety‐two serum samples and 54 vitreous samples were collected from patients with a range of eye diseases including neovascular age‐related macular degeneration (AMD), diabetic retinopathy, retinal vein occlusion, cataract, glaucoma, dry eye disease, macular hole, epiretinal membranes and intraocular lens (IOL) dislocation. Serum and vitreous samples were analysed for immune globuline (Ig) G ADAs to brolucizumab and ranibizumab using indirect enzyme‐linked immunosorbent assay (ELISA). Optical Density (OD) was read at 450 nm (wavelength correction at 550 nm) for ADA level measurements. Results: Presence of brolucizumab ADAs was observed in patients with and without prior brolucizumab exposure. Both the frequency of notable ADA signals (OD > 0.1) and the mean ADA signal in serum samples were higher for brolucizumab than for ranibizumab. Two patients who experienced severe IOI and occlusive retinal vasculitis following intravitreal brolucizumab had high brolucizumab ADA serum levels. In one of these two patients, high brolucizumab ADA levels were also found in vitreous. Another patient developed moderate IOI without retinal vasculitis in the presence of low brolucizumab ADA serum levels. Overall, notable brolucizumab ADA levels were less frequent in vitreous than in the corresponding serum samples but with a tendency for higher prevalence in vitreous from patients with diabetic retinopathy. Conclusion: Brolucizumab ADAs occur with significant prevalence in a typical ophthalmic patient population and may represent a risk factor for IOI and occlusive retinal vasculitis following brolucizumab.